EVALUATION OF FUNCTIONAL OUTCOME OF OPEN REDUCTION & INTERNAL FIXATION AND CONSERVATIVE MANAGEMENT OF TALUS FRACTURES IN TRAUMA PATIENTS - A RANDOMIZED CONTROL TRIAL (The Research of Medical Science Review, 2025)
Background: The talus plays a critical role in ankle joint stability and mobility. Fractures of the talus, although uncommon, are associated with significant morbidity due to its unique vascular anatomy and articular coverage. Objectives: To compare the functional outcomes of ORIF versus conservative management in patients with talus fractures using the AOFAS (American Orthopaedic Foot & Ankle Society) score. Study Design & Setting: This study was conducted at the Department of Orthopedics, Rawalpindi Teaching Hospital, from 16th August 2024 to 15th February 2025. Methodology: A total of 60 with Hawkins Type B, C, or D talus fractures were randomized into two groups: 30 patients received conservative treatment and 30 underwent ORIF. Data were collected using a structured proforma. Functional outcomes were assessed using the AOFAS score at six weeks post-treatment. Data were analyzed using SPSS v23. Chi-square tests were applied to assess associations, with a p-value ≤ 0.05 considered statistically significant. Results: The mean AOFAS score was significantly higher in the ORIF group (60.58 ± 9.42) compared to the conservative group (46.33 ± 10.40), p < 0.001. Impaired outcomes (AOFAS < 50) were more frequent in the conservative group (63.3%) versus the ORIF group (13.3%). Stratified analysis showed significant associations between impaired outcomes and age, gender, and trauma type. Conclusion: ORIF resulted in significantly better short-term functional outcomes compared to conservative treatment for talus fractures. Surgical intervention should be preferred when feasible to optimize patient recovery.